ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN TIKET PO HARAPAN JAYA DI CIPUTAT TANGERANG SELATAN - Najmi Fat-han Alghifari; Aan Purnama (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This research aims to analyze the marketing strategy used to increase ticket sales of PO Harapan Jaya in Ciputat, South Tangerang. The study is based on the rising competition within the land transportation industry, particularly intercity and interprovincial (AKAP) bus services, which is influenced by shifting consumer behavior and the rapid development of digital technology. This study applies a descriptive qualitative method with data collected through interviews, observations, and documentation. SWOT, IFAS, and EFAS analyses were utilized to identify the company’s strengths, weaknesses, opportunities, and threats related to its marketing strategy. The findings indicate that PO Harapan Jaya possesses strong service quality and customer loyalty but faces challenges including increasing competition and limited use of digital marketing. Based on the SWOT analysis, recommended strategies include enhancing digital promotion, expanding partnerships with online ticketing platforms, improving service facilities, and strengthening customer relationships. This research is expected to provide valuable insights for the company in formulating more effective marketing strategies to increase ticket sales. Keywords: Marketing Strategy, Ticket Sales, SWOT Analysis, PO Harapan Jaya, AKAP Transportation.